The effect of Cyanidin‐3‐o‐glucoside on UVA‐induced damage in human dermal fibroblasts. Issue 4 (25th January 2018) - Wu, Shi; Hu, Yunfeng; Li, Zhen; Bai, Weibin; Zhao, Jiayi; Huang, Cuiqin; Li, Qin; Fan, Chongzhu; Deng, Liehua; Lu, Daxiang
Summary: Background/purpose: Ultraviolet‐A (UVA) radiation can induce photoaging and skin cancer, but means to prevent or treat UVA‐induced skin damage require further study. We investigated the effects of cyanidin‐3‐o‐glucoside (C3G), a monomer of anthocyanin, on UVA‐induced damage in primary human dermal fibroblasts (HDFs), and we identify possible mechanisms underlying the protective effects of this compound. Methods: Primary HDFs were pretreated with 80 μmol/L C3G for 2 hours and UVA irradiated at 12 J/cm 2 . The cells were then incubated with 80 μmol/L C3G for 12 hours after irradiation. HDFs were randomly divided into control, UVA treatment, C3G, and UVA treatment plus C3G pretreatment groups. Results: C3G increased the cell viability of primary HDFs and decreased UVA‐induced ROS production and apoptosis rate. Compared to the UVA group, the UVA plus pretreatment with C3G group displayed increased Bcl‐2 expression and Bcl‐2/Bax ratio, decreased cleaved caspase‐3 and p‐P38 levels, and increased ERK phosphorylation; no significant effect on p‐JNK levels was observed. Conclusion: C3G reduced UVA‐induced HDF oxidative damage and apoptosis, likely be related to the down‐regulation of p‐P38, up‐regulation of ERK protein phosphorylation.